Intervention of Fiber-Rich Black Soybean Tofu to Improve Lipid Profile of Type 2 Diabetes Respondents - Nela Eska Putri; Nanda Triandita; Fransiska R Zakaria; Endang Prangdimurti (Jurnal Sains dan Teknologi Pangan, 2023)
This study aims to determine the effect of high-fiber black soybean tofu on improving lipid profiles of type 2 diabetics. The stages of the study consisted of respondent selection, production of high-fiber black soybean tofu, intervention in the treatment group, and analysis of blood lipids. This study used 18 respondents with type 2 diabetes who were divided into 2 groups, namely the intervention group and the control group. The intervention group (n=9) was given 80 g of tofu soup and education for 30 days and the control group (n=9) was not given tofu soup (education). Blood lipid analysis consisted of total cholesterol, HDL-cholesterol, LDL-cholesterol, and triglycerides taken on day 0 and day 30. The results showed that the high-fiber black soybean tofu intervention reduced total cholesterol by 3,56 mg/dL; increased levels of HDL-cholesterol by 4,11 mg/dL; reduced LDL-cholesterol by 5,33 mg/dL, while triglyceride levels increased by 3,33 mg/dL, however, respondents' triglyceride levels were maintained under normal conditions. High-fiber black soybean tofu intervention can potentially improve blood lipids in type 2 diabetes respondents.